Persistent Elevation of Parathyroid Hormone during Pediatric Parathyroidectomy - Gonzalez, Katherine W.; Ferguson, Angela; Wiebold, Amy; Iqbal, Corey; Garg, Uttam (Journal of Pediatric Biochemistry, 2015)
Primary hyperparathyroidism due to adenoma or hyperplasia is often the cause of inappropriately elevated parathyroid hormone in patients with hypercalcemia. Intraoperative monitoring of parathyroid hormone serum concentrations is widely accepted in the adult population, ensuring adequate resection during primary operative exploration. Here, we describe a pediatric case report during which intraoperative hormone monitoring was crucial in directing the operative approach. This symptomatic patient had standard preoperative studies. However, despite an adequate resection of the identified hyperactive tissue, her intraoperative parathyroid hormone concentrations remained inappropriately elevated prompting further dissection of neighboring tissue. A parathyroid adenoma was successfully excised during the operation, preventing further invasive procedures. This report highlights the feasibility of monitoring intraoperatively parathyroid hormone levels in the pediatric population.
Keywords: intraoperative parathyroid hormone; adenoma; hyperparathyroidism